Stone fidelity : marriage and emotion in Medieval tomb sculpture - Barker, Jessica (Lecturer in art history) (Boydell studies in medieval art and architecture., 2020)
Pioneering investigation of the popular ""double tomb"" effigies in the Middle Ages.